Age-related decline of lymphatic drainage from the eye: A noninvasive in vivo photoacoustic tomography study. (May 2020) - Yücel, Yeni H.; Cheng, Fang; Cardinell, Kirsten; Zhou, Xun; Irving, Hyacinth; Gupta, Neeru
Abstract: We aim to determine whether lymphatic drainage from the eye changes with age. Using quantitative photoacoustic tomography, groups of young and older mice were studied in the live state. 10 CD-1 mice of 2–3 months (5M/5F) were studied in addition to 13 older mice of 12–13 months (6M/7F). In each of 23 mice, near-infrared tracer (a near-infrared dye, QC-1 conjugated with Bovine Serum Albumin) was injected into the right eye, and imaging of ipsilateral cervical lymph nodes was performed with laser pulses at 11 different wavelengths prior to and 20 min, 2, 4 and 6 h after injection. Mean pixel intensities (MPIs) of nodes were calculated at each imaging session. The areas under the curves (AUC) were calculated for both groups of mice and compared using the t -test. The slopes of MPI of each region of interest were compared using the linear mixed model before and after adjusting for sex, body weight and intraocular pressure of the right eye. The mean intraocular pressure of right eyes before injection was similar in older and younger groups (12.77 ± 2.01 mmHg and 12.90 ± 2.38 mmHg, respectively; p = 0.888). In each mouse, the photoacoustic signal was detected in the right cervical lymph nodes at the 2-h time point following tracer injection into the right eye. At the 4 and 6 h imaging times, a steady increase of tracer signal was observed. Areas under the curve in the right cervical nodes were decreased significantly in older mice compared to younger mice (p = 0.007). The slopes of MPI in the nodes were significantly decreased in old mice compared to young mice both before and after adjusting for sex, body weight and intraocular pressure of the right eye (p = 0.003). In conclusion, lymphatic drainage from the eye is significantly reduced in older eyes. This finding suggests that impaired lymphatic clearance of aqueous humor, proteins and antigens from the eye may contribute to age-related disease of the eye such as glaucoma and inflammatory eye disease. Highlights: A novel non-invasive photoacoustic imaging approach was used to quantify lymphatic drainage from the eye. Lymphatic drainage from the eye was found to be reduced in older compared to younger mice. Age-related decline of ocular lymphatic function and impaired clearance of proteins from the eye may be relevant to the understanding and treatment of age-related eye diseases.